Measurement and comparison of taekwondo and yongmudo turning kick impact force for two target heights - O'Sullivan, D.; Chung, C.; Lee, K.; Kim, E.; Kang, S.; Kim, T.; Shin, I. (Journal of Sports Science & Medicine, 2009)
The primary purpose of this research was to compare the impact characteristics of Taekwondo (TKD) and Yongmudo (YMD) player's turning kick according to the target height. 5 highly skilled YMD and 5 TKD players participated in this study. To measure the impact force, two accelerometers were fixed to a PVC pipe in a sandbag. Each participant performed 10 turning kicks trunk and face height in random order. Only the trial with the most accurate (most central impact) measurement was used in the statistical analysis (p < 0.05).There was a significant difference for impact force according to the target height approximately 6400 ± 898 N, 6393 ± 1382 N for the mid section and 5419 ± 659 N, 5475 ± 1293 N for the high section of TKD and YMD groups, but not between groups. The swing phase for the TKD group was significantly shorter than the YMD group's. The TKD groups' recovery phase of the trunk height turning kick was significantly shorter. There was a difference in the players' center of mass (COM) movement as the TKD players' moved significantly more forward, suggesting that the TKD players tended to slide towards the target during the execution of the kick. In conclusion, as the turning kick was performed quicker by the TKD players with a similar impact force and more forward motion, it is evaluated to be a better technique of turning kicking.